2007
DOI: 10.1073/pnas.0610813104
|View full text |Cite
|
Sign up to set email alerts
|

Neural interactions between flicker-induced self-organized visual hallucinations and physical stimuli

Abstract: Spontaneous pattern formation in cortical activity may have consequences for perception, but little is known about interactions between sensory-driven and self-organized cortical activity. To address this deficit, we explored the relationship between ordinary stimulus-controlled pattern perception and the autonomous hallucinatory geometrical pattern formation that occurs for unstructured visual stimulation (e.g., empty-field flicker). We found that flicker-induced hallucinations are biased by the presentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 30 publications
4
48
0
Order By: Relevance
“…These results echo experimental findings that show external electric fields can modulated the speed of traveling waves in cortical slice experiments [11]. Recently, it was shown that spatially homogeneous time-periodic inputs give rise to hexagonal or rectangular patterns, depending on the period of the input [34], successfully describing psychophysical experiments regarding flicker phosphenes [35]. Few studies have spoken to the potential effects of transient stimuli on spatiotemporal dynamics of neural fields [24].…”
Section: Introductionsupporting
confidence: 65%
“…These results echo experimental findings that show external electric fields can modulated the speed of traveling waves in cortical slice experiments [11]. Recently, it was shown that spatially homogeneous time-periodic inputs give rise to hexagonal or rectangular patterns, depending on the period of the input [34], successfully describing psychophysical experiments regarding flicker phosphenes [35]. Few studies have spoken to the potential effects of transient stimuli on spatiotemporal dynamics of neural fields [24].…”
Section: Introductionsupporting
confidence: 65%
“…However, the prior probability that two objects could move sufficiently fast between locations to reproduce flicker-stimuli is very low. Indeed such hyperpriors, that flickering stimuli are caused by the motion of a single stimulus, are the cornerstone of many psychophysical and electrophysiological studies of apparent motion (e.g., Billock & Tsou, 2007).…”
Section: Flicker and Swap Rivalrymentioning
confidence: 99%
“…Courtney & Buchsbaum, 1991;Grunfeld & Spitzer, 1995). However, for conscious experience of the hallucination processing that extends to later, extra-sensory cortical areas would be necessary: This is evidenced by Billock and Tsou (2007) who showed that (flicker-induced) hallucinatory-pattern formation is strongly influenced by the presentation of adjacent geometrical forms, thereby indicating that similar cortical processes cooperate to bring about both normal vision, and hallucinatory perception.…”
Section: Introductionmentioning
confidence: 96%